2011
DOI: 10.1080/03079457.2011.588686
|View full text |Cite
|
Sign up to set email alerts
|

Comparativein vivosafety and efficacy of a glycoprotein G-deficient candidate vaccine strain of infectious laryngotracheitis virus delivered via eye drop

Abstract: Infectious laryngotracheitis (ILT) is an acute respiratory disease in poultry that is commonly controlled by vaccination with conventionally attenuated virus strains. Despite the use of these vaccines, ILT remains a threat to the intensive poultry industry. Our laboratory has developed a novel candidate vaccine strain of infectious laryngotracheitis virus (ILTV) lacking glycoprotein G (ΔgG-ILTV). The aim of the present study was to directly compare this candidate vaccine with three currently available commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…Previous in vivo studies have shown significant variations in pathogenicity between different vaccine strains (Kirkpatrick et al, 2006a;Coppo et al, 2011). The findings from the present study provide evidence of differences in viral replication and transmission between vaccine strains.…”
Section: Discussionsupporting
confidence: 63%
“…Previous in vivo studies have shown significant variations in pathogenicity between different vaccine strains (Kirkpatrick et al, 2006a;Coppo et al, 2011). The findings from the present study provide evidence of differences in viral replication and transmission between vaccine strains.…”
Section: Discussionsupporting
confidence: 63%
“…3A) but may explain the lower weight gain in chickens inoculated with ΔgG-ILTV ( Fig. 3B) than in the chickens described previously (17,18).…”
Section: Resultsmentioning
confidence: 74%
“…(12) and 21 days p.i. (18,20) in previous studies using the same commercial enzyme-linked immunosorbent assay (ELISA) kit, a finding that is likely related to the short time that elapsed between inoculation and sampling. Back titration of the inoculum revealed that birds in the ΔgG-ILTV group received 10 0.5 tissue culture infective dose (TCID 50 ) more virus than those in the ΔgGREV-ILTV group (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…different doses of virus and different times between inoculation of each virus) and also studies to assess how ILTV vaccines may be used to limit recombination. Although ILTV vaccines help to prevent disease they do not fully prevent infection or viral replication following challenge [30]. As alphaherpesvirus recombination is closely associated with replication [15] this means there is the potential for ILTV recombination to occur in vaccinated birds.…”
Section: Discussionmentioning
confidence: 99%